Zeichnungen der deutschen Avantgarde. - Weiermair, Peter; Galerie im Taxispalais, Innsbruck; Deuringschlössl, Bregenz; Neue Galerie am Museum Joanneum, Graz; Galerie nächst St. Stephan, Wien (Innsbruck : Galerie im Taxispalais, 1972)
Baselitz, Georg ; Darboven, Hanne ; Erber, Wolfram ; Höckelmann, Antonius ; Immendorff, Jörg ; Jochims, Reimer ; Knoebel, Wolf ; Mocher, Peter ; Palermo, Blinky ; Penck, A.R. ; Polke, Sigmar ; Richter, Gerhard ; Ruthenbeck, Reiner ; Tadeusz ; Walther, Franz Erhard
Zeichnungen der deutschen Avantgarde, Galerie im Taxispalais, Innsbruck, 6.6. - 2.7.1972 ; Deuringschlössl, Bregenz ; Neue Galerie am Museum Joanneum, Graz ; Galerie nächst St. Stephan, Wien
boek
Keywords: Duitsland